New taxa in the third evolutionary lineage of Allium (Amaryllidaceae) - Huang, De-Qing; Friesen, Nikolai; Sun, Hang; Ma, Xiang-Guang (Phytotaxa, 2026)
Molecular phylogenetic studies have confirmed that Allium section Sikkimensia (Traub) N. Friesen represents a well-supported monophyletic unit within the third evolutionary lineage of Allium. However, the sectional name ‘Allium section Sikkimensia’ proposed by N. Friesen (Friesen et al. 2006) is invalid according to Arts. 38.1(a) and 6.10 of the ICN (2025) since its basionym ‘Allium subsection Sikkimensia’ (Traub 1972) lacks an original description or diagnosis (nom. nud.). In accordance with the ICN, we hereby publish a new section corresponding to ‘Allium section Sikkimensia’ sensu N. Friesen, namely Allium section Alpinoprasum sect. nov.; meanwhile, we elevate this taxon to the subgeneric rank and formally name it Allium subgenus Alpinoprasum subgen. nov. Secondly, Allium pinifolium and A. wuzhengyii from southwestern China are described as new species. ITS phylogenetic analyses indicate that A. pinifolium is found within various neighboring populations of A. sikkimense s.l., and that A. wuzhengyii is probably closely related to A. beesianum. The potential reasons underlying their close phylogenetic affinities with A. sikkimense s.l. and A. beesianum are discussed. Detailed morphological descriptions and illustrations are provided for both new species, together with data on their habitats and genome sizes.